Training doctors briefly and in situ to involve their patients in making medical decisions—Preliminary testing of a newly developed module. (18th May 2017) - Kasper, Jürgen; Liethmann, Katrin; Heesen, Christoph; Reissmann, Daniel R; Geiger, Friedemann
Abstract: Objective: To carry out preliminary evaluation of a training module for doctors to enhance their ability to involve their patients in medical decision making. The training refers to the shared decision‐making (SDM) communication concept. Methods: The training module includes a comprehensive manual, a corresponding video tutorial with communication examples and a 15‐minute face‐to‐face feedback session based on an SDM analysis of a consultation recording provided by the trainee. Ten trainees (four neurologists, three dentists, and three general practitioners) participating in the pretest each recorded four clinical consultations (total sample: N=40) and received three training components. After the training, doctors provided feedback on the module's feasibility in a questionnaire. Communication performance of doctors, patients and doctor–patient dyads was assessed by trained observers and self‐assessed by doctors and patients using the MAPPIN'SDM approach. Training effects were determined using Wilcoxon signed‐rank tests comparing baseline values with post‐intervention performance as assessed in the fourth consultations. Results: The face‐to‐face training sessions were short and feasible with regard to clinical reality. Participants considered the training supportive for acquiring SDM skills and recommended more emphasis on the face‐to‐face feedback. Communication improved according to observers rating doctors ( P =.05) and doctor–patient dyads ( P =.07) and to doctors' own judgements ( P =.02). No improvement was observed in patients' SDM behaviour ( P =.11); accordingly, patients' judgements did not indicate improvement ( P =.14). Conclusions: The training is designed to meet clinicians' needs. Improvement of risk communication after training encourages optimization according to doctors' feedback. Following this study, the efficacy of the training is now being examined in a randomized controlled trial.